Hubungan Manajemen Spiritual dan Peran Kiai dalam Membangun Karakter Religius Siswa SDI Al Munawwar Tulungagung - Mustika Nirmala; Anggara Dwinata Dwinata (Journal of Islamic Education and Learning, 2026)
Religious character education is an important step for elementary school educational institutions in developing students' attitudes, morals, and character. Building religious character requires the important role of religious scholars (kyai) and mature spiritual management. This is a concrete strategy in anticipating the dynamics of negative influences in the era of disruption. The method used is a quantitative approach with a correlation study design. The study was conducted on students of Al Munawwar Islamic Elementary School, Tulungagung, with a sample of forty students with achievement indicators for each variable. The results showed that the contribution or determination coefficient was 79.2% and the F-count value was 5.347 > F-table of 3.195. When viewed from the probability value (sig.) - obtained at 0.01 < 0.05 (significance level). So it can be concluded that spiritual management and the role of kiai can build the religious character of students of Al Munawwar Islamic Elementary School, Tulungagung.